The Palgrave Handbook of Blue Heritage - Boswell, Rosabelle; O'Kane, David; Hills, Jeremy (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This handbook is unique in its consideration of social and cultural contributions to sustainable oceans management. It is also unique in its deconstruction of the hegemonic value attached to the oceans and in its analysis of discourses regarding what national governments in the Global South should prioritise in their oceans management strategy. Offering a historical perspective from the start, the handbook reflects on the confluence of (western) scientific discourse and colonialism, and the impact of this on indigenous conceptions of the oceans and on social identity. With regard to the latter, the authors are mindful of the nationalisation of island territories worldwide and the impact of this process on regional collaboration, cultural exchange and the valuation of the oceans. Focusing on global examples, the handbook offers a nuanced, region relevant, contemporary conceptualisation of blue heritage, discussing what will be required to achieve an inclusive oceans economy by 2063, the end goal date of the African Union's Agenda 2063. The analysis will be useful to established academics in the field of ocean studies, policymakers and practitioners engaged in research on the ocean economy, as well as graduate scholars in the ocean sciences. Rosabelle (Rose) Boswell is an anthropologist and poet. She is also an NRF-DSI South African Research Chair of Ocean Cultures and Heritage. She is based at Nelson Mandela University, South Africa. David O'Kane is a graduate of the National University of Ireland and holds a doctorate from Queen's University Belfast. He is an associate of the Max Planck Institute for Social Anthropology. Jeremy Hills is a Professor at USP and a Chartered Environmentalist with over 20 years of experience of professional research and consultancy in coastal and marine environments. .
1. Introduction: Blue Heritage, Human Development and the Climate Crisis -- Part 1: Humans and Humanities in Ocean Heritage -- 2. The Evolutionary Roots of Blue Heritage -- 3. Islands and the Sea -- 4. Oceanic humanities for Blue Heritage -- 5. World and Marine Heritages -- Part 2: Historical, Cultural and Literary Perspectives -- 6. Jeremy Hills Greek Study 1 -- 7. Tales of Ocean, Migration And Memory in Ancestral Homespaces In Goa -- 8. Salt, Boats and Customs: Maritime Princely States in Western India, 1910-1932 -- 9. Navigating Environment, History and Archaeology in Portsmouth Island, USA -- 10. Multi-spirited Waters in Lynton Burger's She Down There -- 11. Women Rising, Women Diving in Vanuatu and Australia -- 12. Speaking with The Sea: Divination and Identity in South Africa -- Part 3: Environmental, Legal and Political Realities -- 13. Selo! Oral Accounts of Seychelles' Maritime Culture -- 14. Waking up to Wakashio: Marine and Human Disaster in Mauritius -- 15. Blue heritage among Fishermen of Mafia Island, Tanzania -- 16. Blue Heritage in the Blue Pacific -- 17. Policies, Epistemologies in inclusive oceans management in Sierra Leone -- 18. Navigating a Sea of Laws: Small-scale fishing communities and Customary Rights in Ghana and South Africa -- 19. Narratives of Non-compliance in 'Tuesday non-fishing day' in Ghana -- 20. Lalela uLwandle: an experiment in plural governance discussions -- 21. 'Other' Social Consequences of Marine Protection in Tsitsikamma, South Africa -- 22. Sustaining the Underwater Cultural Heritage -- 23. Underwater Cultural Heritage, Poverty and Corruption in Mozambique.
Keywords: Environmental sciences-Social aspects; Human geography; Environmental geography; Human ecology-History.; Cultural property-Protection.; Historic preservation; Environmental Social Sciences; Human Geography; Integrated Geography; Environmental History; Conservation and Preservation